Patient self-management of anticoagulation therapy: a trial-based cost-effectiveness analysis. - Jowett, S; Bryan, S; Murray, E; McCahon, D; Raftery, J; Hobbs, F; Fitzmaurice, D (2006)
Demand for anticoagulation management is increasing due to an expansion of clinical indications for therapy. One possible model of care to meet demand is patient self-management (PSM), beneficial to patients who need control over their condition. This study aimed to determine the cost and cost-effectiveness of PSM of anticoagulation compared with routine clinic-based care for patients receiving long-term anticoagulation. A cost-utility analysis was conducted alongside a randomised controlled trial; 617 patients were recruited and followed up for 12 months. There was no significant difference in mean quality-adjusted life years (QALYs) between groups - after adjusting for baseline, the mean difference in QALYs was 0.009 (95% CI, -0.012 to 0.030). Overall mean healthcare costs in the PSM arm were significantly higher at pounds sterling 417 (CI pounds sterling 394- pounds sterling 442) compared with pounds sterling 122 (CI pounds sterling 103- pounds sterling 144) in the control arm. Therefore, using a formal cost-effectiveness analysis, PSM of anticoagulation does not appear to be cost-effective. However, PSM may have other benefits in relieving pressure on traditional clinic-based care, and the cost-effectiveness of this model of care for some subgroups of anticoagulation patients needs to be explored further.